Peran Pendidikan Agama Dalam Membentuk Manusia Yang Berkeadaban Publik - Athok Fu'adi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This article discusses juvenile delinquency, corruption, sexual harassment in public, which led to violent seizure of land which led to lives lost, a reckless driver, these are the loss of public civility. Problems that can occur due to economic factors, religious education is not wearing or doing in everyday behavior, which raised the question of how the role of religious education in shaping a civilized human being public ?. Man is a creature of the most perfect, there are many potential inherent in man, as leader of this earth, the caliph then humans have a relationship with the human, social and God.